CLEO®/Europe-EQEC 2019, one page summary template femtosecond covariance spectroscopy - Giusti, Francesca; Marciniak, Alexandre; Montanaro, Angela; Sparapassi, Giorgia; Glerean, Filippo; Marcantoni, Stefano; Benatti, Fabio; Asban, Shahaf; Mukamel, Shaul; Fausti, Daniele (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
I will review the possibility to retrieve nonlinear responses in complex materials by measuring noise correlations of classical and quantum nature.
CRIS-Team Scopus Importer:2022-07-20